Identity styles and academic status of Guilan University of Medical Sciences - Shahrokh Maghsoudi; Maedeh Rahimi; Abdolhosein Emami Sigaroodi; Ehsan KazemNezhadLeily (Guilan University of Medical Sciences, 2015)
Introduction: The educational status is the more important purpose of the head of educational development programs in every country. the purpose of the educational institutions, is based on increasing academic success Therefore review and evaluation of students' achievement during study , investigation of cognitive factors and social influence including identity are indispensable elements for improving the quality of education in universities. Objective:, in this study we examined the association between educational status and identity style. Methods: This cross-sectional study is a descriptive - analytical study which was conducted on 371 students of Guilan University of Medical Sciences. The samples were selected using a stratified systematic. The questionnaire was consist of demographic characteristics and standard questionnaire-style identit, respectively. In order to evaluate the educational status, final mark of students were applied. Data were analyzed using parametric statistical tests (mean ± SD) and bread-parametric (Spearman and Mann-whitney and kruskal-wallis). Result: Spearman's test showed that the normative identity style (P<0/03) and commitment (P<0/001) is correlated with the average total students. Conclusion: there was correlation between normative identity style and commitment statistically. . Consequently it seems that for educational progress achievement in each country, the identity and psychosocial status of students is essential.